Fatigue damage prediction of ship rudders under vortex-induced vibration using orthonormal modal FSI analysis. (March 2023) - Jang, Won-Seok; Choi, Woen-Sug; Choi, Hyun-Gyu; Hong, Suk-Yoon; Song, Jee-Hun
Abstract: Recently, the fatigue failure of ship rudders owing to vortex-induced vibration has increased as commercial ships become faster and larger. However, previous methods are inappropriate for fatigue failure prevention owing to the lack of fluid–structure interaction considerations. This study aims to develop a fatigue damage prediction method that can be applied at the design stage to prevent fatigue failure of ship rudders under vortex-induced vibration. The developed prediction method employed the fluid–structure interaction (FSI) method to properly consider the fluid–structure interaction and implemented orthonormal mode shapes to reflect the complex geometry and boundary conditions of the ship rudders. For validation, vortex-induced vibration of the hydrofoil model was obtained using the developed method, and the prediction results matched well with the experimental results. Then, the fatigue damage of the ship rudder model under vortex-induced vibration was predicted using the developed method, and their characteristics are discussed. The stress distribution obtained using the developed method matched well with the geometrical characteristics of the ship rudders. The potential for fatigue failure due to the resonance of vortex-induced vibration was expected by comparing the stress distributions for various flow velocities to the S–N curves provided by the DNV classification. Highlights: Former FSI method for ship rudders is limited to cantilevered foil structures. Modal characteristics of ship rudders cannot be obtained with the former FSI method. Orthonormal modes were implemented in the FSI method to predict the characteristics. The implementation enables vortex-induced vibration prediction of ship rudders. Predicted vibration results enable the fatigue damage prediction of ship rudders.